Effect of fertilizers' types on yield parameters, sweetness and nutritional quality of carrot (Daucus carota L.) genotypes - Djoufack Tonfack Maxime Merlin; Foko Kouam Edith Marius; Kouam Eric Bertrand; Anoumaa Mariette; Kaktcham Pierre Marie; Zambou Ngoufack François (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
Farmers usually rely on various fertilizers to enhance the yield and productivity of crop species. However, these fertilizers are likely to affect performances and qualities traits of crops. To bring out the interaction between agricultural inputs and carrots characteristics, we studied their effect on yield attributes and chemical composition in three varieties of Daucus carota L.. Some yield parameters and chemical components of carrot roots were determined. Carrot's sweetness was also measured using a hedonic test. Fertilizers had a significant effect (p<0.05) on both yield attributes and chemical components except moisture content. The results show that chemical components were significantly different between carrot varieties. Interactions between fertilizer treatment and variety were significant for most yield and chemical characteristics. Yield, carbohydrates and carotenoids were significantly higher when using chicken manure as fertilizer. Compost fertilizer enhances important reducing sugars. Treatment using NPK fertilizer induced more proteins and iron. Calcium level was high when using either compost or chicken manure as fertilizer. Better Sweetness was obtained when using chicken manure. Chicken manure or compost; used alone or associated with NPK fertilizer increased agronomic and nutritional characteristics and in carrots.